Implementasi Blanded Learning dalam Meningkatkan Motivasi Belajar Fiqih Kelas VII di MTs Darun Najah Karangploso - Nisa', Khoirun; Hilma, Nuzulul Alfia (JoEMS (Journal of Education and Management Studies), 2023)
Success in the learning process will be achieved when the teachersuccessfully transfers knowledgeto students. Therefore, the right learning strategies and models are needed, one of which is theblanded learning model. The blanded learning model can also be used as a solution to the problemof low student learning motivation. The purpose of this study is to find out how the implementationof the blanded learning model in increasing the learning motivation of CLASS VII students in fiqhsubjects at MTs Darun Najah, Ngijo-Karangploso. This research uses qualitative methods, with aqualitative descriptive approach. The data sources in the study are primary and secondary data.Primary data were taken from interviews, interviews conducted with the head of the Madrasah, andteachers of class VII fiqh subjects at MTs Darun Najah. Secondary data is taken from field recordsof observations, and documentation in the form of photos and audio. The resultsof this study provethat blanded learning-based learning is able to increase the learning motivation of class VIIstudents in MTs Darun Najah, especially in the subject of fiqh learning. However, in itsimplementation there are several obstacles, including that there are still some teachers who do notfully understand the concept of blanded learning at MTs Darun Najah, and the internet networkwhich is still often problematic, so that it can trigger the inefficiency of learning using the blandedlearning learning model at MTs Darun Najah.